Combination of Cordycepin and Apatinib Synergistically Inhibits NSCLC Cells by Down-Regulating VEGF/PI3K/Akt Signaling Pathway - Liao, Xiaozhong; Tao, Lanting; Guo, Wei; Wu, Zhuo-Xun; Du, Haiyan; Wang, Jing; Zhang, Jue; Chen, Hanrui; Chen, Zhe-Sheng; Lin, Lizhu; Sun, Lingling (Frontiers in Oncology, 2020)
Background: The application of apatinib is immensely limited by its acquired drug resistance. This research investigates whether cordycepin, a component from Cordyceps could synergize with apatinib to improve its anticancer effect on non-small cell lung cancer (NSCLC) cells. Methods: The NSCLC cell lines A549, PC9 and H1993, and human bronchial epithelial (HBE) cell line Bears-2B were used in this study. Cell counting kit 8, colony formation assays, wound healing assay, transwell assay and flow cytometry analysis were performed to assess the cell viability, the migration ability and invasion ability of the cells. Kyoto Encyclopedia of Genes and Genomes (KEGG), western blotting and molecular docking was applied to analyze the possible pathways affected by cordycepin. Results: The combination of cordycepin and apatinib in a ratio of 5:1 synergistically reduced proliferation of NSCLC cells, inhibited cell migration and invasion, increased cell apoptosis by altering cell cycle in NSCLC A549 and PC9 cells. The VEGF/PI3K/Akt pathway was inhibited after treatment with cordycepin and apatinib. Conclusions: Our findings demonstrated that the combination of cordycepin and apatinib has synergistically anticancer effect on NSCLC cells by down-regulating VEGF/PI3K/Akt signaling pathway. This result indicated that cordycepin and apatinib could be a promising drug combination against NSCLC.